In Situ WetSTEM Observation of Gold Nanorod Self-Assembly Dynamics in a Drying Colloidal Droplet. (18th March 2014) - Novotný, Filip; Wandrol, Petr; Proška, Jan; Šlouf, Miroslav
Abstract Direct in situ visualization of nanoparticles in a liquid is an important challenge of modern electron microscopy. The increasing significance of bottom-up methods in nanotechnology requires a direct method to observe nanoparticle interactions in a liquid as the counterpart to the ex situ electron microscopy and indirect scattering and spectroscopy methods. Especially, the self-assembly of anisometric nanoparticles represents a difficult task, and the requirement to trace the route and orientation of an individual nanoparticle is of highest importance. In our approach we utilize scanning transmission electron microscopy under environmental conditions to visualize the mobility and self-assembly of cetyltrimethylammonium bromide (CTAB)-capped gold nanorods (AuNRs) in an aqueous colloidal solution. We directly observed the drying-mediated AuNR self-assembly in situ during rapid evaporation of a colloidal droplet at 4°C and pressure of about 900 Pa. Several types of final AuNR packing were documented including side-by-side oriented chains, tip-to-tip loosely arranged nanorods, and domains of vertically aligned AuNR arrays. The effect of local heating by electron beam is used to qualitatively asses the visco-elastic properties of the formed AuNR/CTAB/water membrane. Local heating induces the dehydration and contraction of a formed membrane indicated either by its rupture and/or by movement of the embedded AuNRs.